Perceptions of Students in Different Phases of Medical Education of Educational Environment: Ankara University Faculty of Medicine - Demirören, M. (Medical Education Online, 2008)
The present study was undertaken to identify the perceptions of students about their educational environment in a newly restructured curriculum. The Turkish version of the DREEM questionnaire (total score: 200) was used to diagnose the strengths and weaknesses of the curriculum which is known to be a major determinant of educational environment. Five hundred fifty three students (years 1, 3, 5) voluntarily replied to the questionnaire. The mean DREEM score was found to be 117.63 (58.8%). The mean scores for the whole DREEM questionnaire and the five essential domains were found to be significantly different in different phases of medical education. The scores were found to be highest (123.65) for year 3 students and lowest (109.39) for year 5 students. The results are the first data of a curriculum reform obtained from the students about the educational environment and give important feedback to curriculum planners and change managers of the faculty for necessary improvement.